Governance Improvement Post E-government Adoption: A Case of Jordanian Public Entities - Al-Smady, Ahnaf Ali (International Review of Management and Marketing, 2017)
This study examines the efficacy of governance after the adoption of e-governance among Jordanian governmental organisations. E-government refers to ICT mechanisms which purportedly lead a better governance. Internal end-user satisfaction is one measure of the efficacy of internal e-governance. End-user satisfaction comprises content, accuracy, format, ease of use and timeliness. Different from existing academic research, the present study analyses the adoption of e-government among Jordanian governmental organisations. This topic has not previously been examined. A survey of at eight Jordanian governmental entities at the officers and directors level is employed as the data collection tool. T-test and non-parametric Wilcoxon-test are used to examine a cross section of data from eight Jordanian governmental entities to test the research hypotheses. The present study finds that there is a statistical difference of end-user satisfaction after e-government adoption in terms of content; accuracy; format; ease of use and timeliness. The paper makes a significant contribution by testing the improvements in governance after the adoption of e-government among Jordanian governmental entities. Furthermore, the paper enhances the understanding of Jordan’s e-government programme. Keywords: E-government, Governance, End-user Satisfaction. JEL Classifications: M1, O32, O14